Monetary policy and the US housing market: A VAR analysis imposing sign restrictions. - Vargas-Silva, C (Elsevier, 2008)
This article examines the impact of monetary policy shocks on the US housing market using an identification procedure similar to the one suggested by Uhlig [Uhlig, H., 2005. What are the effects of monetary policy on output? Results from an agnostic identification procedure. Journal of Monetary Economics 52, 381-419]. The identification procedure imposes sign restrictions on the response of some variables for a certain period. No restrictions are placed on the response of the housing variable. Overall, the results indicate that housing starts and residential investment respond negatively to contractionary monetary policy shocks. However, the magnitude of the impact is sensitive to the selection of the horizon for which the restrictions hold. Moreover, a comparison of the results with those obtained from a conventional Choleski decomposition, suggests that the impact of monetary policy on the housing market is much less certain under the sign restrictions approach.